Microbially influenced corrosion: towards an interdisciplinary perspective on mechanisms - Little, Brenda J. (2022)
A perspective is provided on mechanisms for microbially influenced corrosion by sulfate-reducing bacteria and metal-oxidizing bacteria. The authors discuss the confusion introduced by cross-disciplinary discussions of MIC mechanisms and the divergent terminologies used by microbiologists and electrochemists, e.g. “anaerobic” and “direct electron transfer.” Examination of the cathodic depolarization theory for corrosion of carbon steel by sulfate-reducing bacteria suggests that the theory cannot explain the observations. Stainless steels containing <20% chromium are vulnerable to pitting in the presence of iron and manganese oxides produced by iron- and manganese-oxidizing bacteria, respectively. However, mechanisms for pitting differ between the two oxides. In all cases, understanding mechanisms for microbially influenced corrosion must consider the environment, i.e., the composition of the electrolyte, in addition to the vulnerability of the material in the presence of putative microorganisms. Significant opportunity exists for more integrated approaches to interdisciplinary research and open discourse.